Stepping up [ how taking responsibility changes everything - Izzo, John B. [ (John Baptist)] , 1957- (Berrett-Koehler Publishers, 2012)
Bestselling author John Izzo brings together his distinctive mix of inspiring story-telling and practical advice to tell how we can more effectively bring about positive change by taking responsibility in our work, personal lives, and communities.